Identifying shrines area using RADARSAT Lembah Bujang, Kedah, Malaysia - Hj. Mohd. Noor, Norzailawati; Roslan, Shairatul Akma; Md Ali, Zuraini; Abdullah, Alias (2016)

(untitled)
Lembah Bujang was an international cultural and commercial crossroad 2000 years age. Its history, its potential, economic and socio – cultural administrator and significance, its art and architecture, its diplomatic relationship and so on offer fertile ground for scholar investigation. However, the issue on the pre-historic ruins as archaeological sites in Lembah Bujang were secretly demolished by a modern development brings a further analysis. The aim for this research is to identify a potential shrines area in two study areas consist of Lembah Bujang and Sungai Batu using RADARSAT and GIS techniques in conserving the historical site. The multi-temporal images of RADARSAT for years 2003 and 2014 have been used with two techniques in identifying potential shrines consist of Local Adaptive Filtering and Feature Extraction have been used and tested three selected study areas with using processing software of ENVI 4.8 and ArcGIS. The finding shows that The Local Adaptive Filtering on GAMMA Map filter is one of the best techniques in identifying potential shrines areas at once as guidance to pursuing an area as official gazette historical site in Malaysia as well contribute in the chronology of the land use development planning in Lembah Bujang, simultaneously assist in making recommendations in land use planning guidelines for preservation and conservation in the heritage site.